The most influential factors of english oral tasks on the learners’ fluency level in that language: case of Advanced Intensive English I curses of the Foreign Language Department at the University of El Salvador - Martínez Doradea, Karen Elizabeth
Learning a second or foreign language is a process that concerns to the development of the four main skills (reading, writing, listening, and speaking). These four skills are of great importance to be developed in the learning process since all of them supplement each other and are the key to reach the language proficiency. In the teaching-learning process teachers make use of a diverse number of techniques to develop each of the four main skills. However, in many cases teachers give more emphasis to the development of one skill than to the others, the speaking skill being the ability on top to be developed. The speaking skill has different sub skills that need to be developed in order for a learner to be proficient in this ability. Some of these sub skills are pronunciation, accuracy, and fluency. The last one is considered fundamental in the oral skill. So, speaking English fluently is to express a wide range of ideas without unnecessary pauses or breakdowns in communication, and speaking English accurately is to use an acceptable standard of pronunciation and grammar when communicating by Richards & Sandy, (1998). In the Intensive English courses at the Foreign Language Department at the University of El Salvador, the students have the chance to develop their speaking skill by practicing new vocabulary in the classroom, and being part of a different type of oral tasks like explaining a topic, oral discussions, performing role plays, etc. However, during those courses there are different factors that influence the students‟ oral practice, impacting their performance and hindering the development of their oral fluency.